ORDINARY KRIGING DALAM ESTIMASI CURAH HUJAN DI KOTA SEMARANG - Ahmat Dhani Riau Bahtiyar; Abdul Hoyyi; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
In a measurement of rainfall data, not all points are gauges because of a limitation. Given these limitations, a method is needed to estimate a value for points that are not measurable. Kriging as geostatistical analysis used in the estimation of a value in a point which is not sampled based sample points in the surrounding areas by taking into account the spatial correlation using a spatial weighting, where the correlation is shown by the variogram. Ordinary Kriging is the most widely used. By using the experimental variogram were compared with some theoretical variogram (Exponential, Gaussian, Spherical) selected one of the best semivariogram models to estimate the value that want to find. In this study, conducted rainfall estimates in Semarang in February where the result obtained is the value of rainfall each district and village